Identifikasi dan Assesmen Pengembangan Bisnis, Potensi Bisnis dan Produk Exsting - Sultan; Puspitasari, Dewi; Syafruddin, Reni Fatmasari; Asgaf, Khalifah; Abdullah, Andi Aziz; Hutabarat, Zuhri Hutabarat (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam (IAI) Al-Aziziyah Samalanga, 2024)
Identification and Assessment of business development, business potential and existing products need to be carried out in order to remember the existence and increasing critical and very critical land in the Bonehau Kalumpang Forest Management Unit, caused by land degradation and forest conversion due to the expansion of agricultural and plantation land, as well as construction and/or improvement of road access to the area. The rate of deforestation and land degradation in the Forest Management Unit needs to be balanced with efforts to restore, maintain and improve the function of the forest and land. Thus, the carrying capacity, productivity, and role of the forest and land in maintaining the life support system can be increased. The Implementation Method of this activity starts from the preparation stage, data collection, both primary and secondary data, processing and analysis of data related to superior commodities, business feasibility and recommendations for further activities. Based on the results of the Identification and Assessment of business development, business potential and existing products, several recommendations are proposed, including (1) Agroforestry Development in Salutiwo Village (2) Establishment of village cooperatives, (3) Inventory of the number of aren stands located in and outside the forest area in Salutiwo Village (4) Increasing community knowledge and skills through mentoring and training from upstream to downstream.